Carbohydrate metabolism in the developing endosperm of rice grains - Nakamura, Y.; Yuki, K.; Park, S.-Y.; Ohya, T.
The metabolism of carbohydrates in developing rice endosperm was characterized by a comparison of levels of activities of 33 major enzymes between the endosperm and green leaves of rice. Activities of ADPglucose pyrophosphorylase, starch synthase and branching enzyme (Q-enzyme), compared on the basis of soluble protein content, were markedly higher in endosperm than in green leaves. The high levelsof Q-enzyme may be responsible for the efficientproduction of starch in the rice endosperm. The GIP is converted to starch by the concerted reactions of ADPglucose pyrophosphorylase, starch synthase and Q-enzyme.measurement of levelsof metabolic intermediates and the localization of key enzymes in isolated amyloplasts from rice endosperm support the view that sucrose is metabolized in the cytoplasm via the pathway: sucrose-+UDPglucose-+hexose-P-+FBP -+triose-P. Triose-P then enters the amyloplast, where it is converted to G1P via FBP and, finally
Keywords: ADPGLUCOSE PYROPHOSPHORYLASE; AMYLOPLAST; ENDOSPERM; Q-ENZYME; RICE TORYZA SATIVA L.); STARCH METABOLISM